(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2022)
Naming of a kind that relegates unwelcome poor strangers is a current challenge in countries that continue to experience substantial migration of destitute individuals. On the basis of African moral philosophy, and specifically an ubuntu/hunhu ethical theory, I examine the ethics of naming and particularly the concern that some names relegate unwelcome poor strangers in the host society. First, I discuss the problem of terms such as “foreign” and the relegation of poor migrants. Secondly, I draw attention to the ethic I am going to use to evaluate names, probing the African philosophy’s understanding of stranger and brother in terms of human dignity. Thirdly, I apply my favored dignity-based ethic to contemplations of naming, demonstrating which kinds of names are demeaning, which instead are apposite, and how various agents should change theirpresent practices. What is distinct and new in this philosophical investigation on naming and the relegation of poor immigrants is that I appeal to ubuntu moral theory and propose positive alternatives about which names should be used along with recommendations for change of practice.